The Dynamics of Election Disputes in Indonesia Case Study of Decision Number 36 / PHP. GUB-XVI / 2018 - Rajib, Rayi Kharisma; Karismawan, Yogi (Law Research Review Quarterly, 2018)
Election disputes in Indonesia are a problem that is often faced when Indonesia conducts elections. Losing and winning in elections is a matter of course. However, defeat in elections is often unacceptable. Losing from the election seems to be the end of the world, so that justifies any means to question it. The potential for disputes arises when the official results are announced by the General Election Commission (KPU) because there are parties who find violations and feel disadvantaged but there are also those who sue only to try their luck because they have not been able to accept defeat in democratic elections. Election disputes cause people to break up into groups that blame each other and make the excuses of those who lose the election to sue that fraud occurs in elections and as if they did not accept the results announced by the General Election Commission (KPU).